Cover Picture: Novel Fluorescent Chemosensor for Detection of F− Anions Based on a Single Functionalized Pillar[5]arene Iron(III) Complex (Chin. J. Chem. 12/2016). Issue 12 (December 2016) - Zhang, Youming; Su, Junxia; Li, Qiao; Li, Wenting; Liang, Guoyan; Li, Hui; Ma, Haixia; Lin, Qi; Yao, Hong; Wei, Taibao
Abstract : The cover picture shows the possible complex process between PN‐Fe and fluoride. Pillar[ n ]arenes have the symmetrical structure, and are easier to functionalize than other macrocyclic hosts. In this paper, a single functionalized pillar[5]arene could coordinate Fe 3+ ion and form metal complex. The complex was utilized to detect F − anion as a fluoride fluorescence sensor in DMSO solution. The reversible competitive coordination process of Fe 3+ ion by F − anion revealed the essence of the fluorescence change. More details are discussed in the article by Zhang and Wei et al . on page 1263–1267.